Anorexia nervosa versus bulimia nervosa: differences based on retrospective correlates in a case-control study - Machado, Bárbara César (2017)
Objective This study is the result of two Portuguese case– control studies that examined the replication of retrospective correlates and preceding life events in anorexia nervosa (AN) and bulimia nervosa (BN) development. This study aims to identify retrospective correlates that distinguish AN and BN Method A case–control design was used to compare a group of women who met Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria for AN (N = 98) and BN (N = 79) with healthy controls (N = 86) and with other psychiatric disorders (N = 68). Each control group was matched with AN patients regarding age and parental social categories. Risk factors were assessed by interviewing each person with the Oxford Risk Factor Interview. Results Compared to AN, women with BN reported significantly higher rates of paternal high expectations, excessive family importance placed on fitness/keeping in shape, and negative consequences due to adolescent overweight and adolescent objective overweight. Discussion Overweight during adolescence emerged as the most relevant retrospective correlate in the distinction between BN and AN participants. Family expectations and the importance placed on keeping in shape were also significant retrospective correlates in the BN group.